2020
DOI: 10.3390/ijms21144990
|View full text |Cite
|
Sign up to set email alerts
|

Selectively-Packaged Proteins in Breast Cancer Extracellular Vesicles Involved in Metastasis

Abstract: Cancer-derived extracellular vesicles are known to play a role in the progression of the disease. In this rapidly-growing field, there are many reports of phenotypic changes in cells following exposure to cancer-derived extracellular vesicles. This study examines the protein contents of vesicles derived from three well-known breast cancer cell lines, MCF-7, MDA-MB-231 and T47D, using peptide-centric LC-MS/MS and cytokine multiplex immunoassay analysis to understand the molecular basis of these changes. Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Extracellular vesicles (EVs) have gained substantial traction in recent years due to the cargo they envelope and transport between cells [ 24 ]. Recent studies have indicated the EV cargo is selectively packaged and not a random grouping of local molecules as a waste removal mechanism [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular vesicles (EVs) have gained substantial traction in recent years due to the cargo they envelope and transport between cells [ 24 ]. Recent studies have indicated the EV cargo is selectively packaged and not a random grouping of local molecules as a waste removal mechanism [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…EVs were isolated similarly to the procedure outlined in Dalla et al [ 11 ], where growth medium was collected from each ADSC cell sample (abdomen, thigh, and chin), and EVs were isolated by differential centrifugation. Media from each cell sample was centrifuged at 20,000× g for 1 h at 4 °C to pellet EVs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lau et al established an in vitro model of breast cancer and found through microarray analysis that exosomes derived from breast cancer cells could process the transcription of salivary exosomes, thereby changing the content of the salivary exosome. 42 In a mouse model, exosomes secreted by pancreatic cancer cells were able to regulate the transcription of genes in the saliva, and further, pancreatic cancer-specific transcriptional genes were identified as having increased expression in salivary exosomes, indicating the presence of markers of pancreatic cancer cells in salivary exosomes. 43 Sun et al used quantitative methods to compare the salivary exosome proteomics profile of normal subjects and patients with lung cancer, and confirmed that four proteins (BPIFA1, CRNN, MUC5B, and IQGAP) derived from lung tissue cells and could be used for non-invasive detection of lung cancer, and further, approximately 80% of the proteins in salivary exosomes and serum exosomes were shared.…”
Section: Role Of Salivary Exosomes In Diagnosis and Prognosis Evaluation Of Malignant Tumorsmentioning
confidence: 98%
“…In addition to their physiological roles, EVs may also play an important role in several pathological conditions [ 27 ]. Therefore, they have attracted increasing attention as biomarkers [ 28 , 29 , 30 , 31 ] in the past few years. Moreover, EVs are also promising therapeutic tools.…”
Section: Introductionmentioning
confidence: 99%